2002
DOI: 10.1006/mthe.2002.0598
|View full text |Cite
|
Sign up to set email alerts
|

CpG-Depleted Plasmid DNA Vectors with Enhanced Safety and Long-Term Gene Expression in Vivo

Abstract: Systemic delivery of cationic lipid-plasmid DNA (pDNA) complexes induces an acute inflammatory response with adverse hematologic changes and liver damage. Immunostimulatory CpG motifs in the pDNA are known to contribute substantially to this response. Here we constructed a pDNA vector (pGZB) that has been depleted of 80% of the CpG motifs present in the original vector. Compared with the unmodified vector, systemic administration of pGZB induced considerably fewer changes in blood parameters, reduced levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
165
2
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(177 citation statements)
references
References 30 publications
8
165
2
2
Order By: Relevance
“…35 In similar reports, 36,37 it was verified that CpG dinucleotides could negatively affect transgene expression from pDNA in vivo, even with linearization of the transgene expression plasmid before hydrodynamic injection. Finally, other groups have reported the negative effect of CpG methylation in vitro, 38 and recently the extensive methylation of CpG islands of a CMV promoter-driven adenoviral vector following delivery into the muscles of mice was shown, with methylation levels similar to our results.…”
Section: Persistent Expression In Vivo From S/mar Plasmidmentioning
confidence: 81%
“…35 In similar reports, 36,37 it was verified that CpG dinucleotides could negatively affect transgene expression from pDNA in vivo, even with linearization of the transgene expression plasmid before hydrodynamic injection. Finally, other groups have reported the negative effect of CpG methylation in vitro, 38 and recently the extensive methylation of CpG islands of a CMV promoter-driven adenoviral vector following delivery into the muscles of mice was shown, with methylation levels similar to our results.…”
Section: Persistent Expression In Vivo From S/mar Plasmidmentioning
confidence: 81%
“…Reducing the host inflammatory response to non-viral GTAs by minimizing the CpG content of the plasmid DNA results in a pronounced extension of the duration of transgene expression. 44 Therefore, to treat chronic lung diseases such as CF, non-viral gene transfer must be optimized at the level of plasmid and formulation in order to be as invisible as possible to the host innate immune surveillance systems.…”
Section: Discussionmentioning
confidence: 99%
“…Hong et al suggested that the CpG dinucleotides may undergo de novo methylation in plasmid DNA in mammalian cells [6]. Moreover, transgene expression was reportedly enhanced when fewer CpG sequences were present in the plasmid DNA [7], implying that CpG methylation suppressed transgene expression.…”
Section: Introductionmentioning
confidence: 99%